Investigating The Role of Quality Dimensions in Enhancing Customer Satisfaction Across Industries - Surono Surono; Soerjanto Soerjanto (Politeknik Siber Cerdika Internasional, 2025)
This study examines the impact of quality dimensions on customer satisfaction across various industries. Using a mixed-method approach, the research identifies Service Quality and Process Quality as the most significant factors influencing customer satisfaction. Service Quality positively impacts customer experience, while Process Quality negatively affects satisfaction due to inconsistencies in operations. The influence of quality dimensions varies by industry: service industries prioritize service quality, manufacturing emphasizes product and process quality, and digital industries focus on innovation and usability. The findings support a holistic evaluation model for quality, integrating key quality dimensions tailored to industry needs. Strategic recommendations include enhancing service quality, optimizing processes, leveraging data-driven feedback, and aligning quality strategies with industry characteristics. This research provides actionable insights for businesses to improve customer satisfaction, foster loyalty, and maintain a competitive advantage.